Female pair/dance figure skaters' self-reported attitudes, behaviors and perceptions related to weight loss. - Taylor, Gail M. (University of Ottawa (Canada), 1998)
The purpose of this thesis was to examine the self-reported eating attitudes/behaviors behaviors, as well as weight loss pressures in female pair/dance figure skaters. Two separate studies were completed in order to examine these issues. Forty-one pair and dance female figure skaters (26 pairs, 15 dance) completed two questionnaires that tapped into whether the figure skaters exhibited disordered eating tendencies (EDI), and whether weight loss pressures were evident in this sporting population (SKATE Scale). Results from the EDI indicated that a significant number of the skaters had self-reported eating attitudes and behaviors analogous to individuals with disordered eating tendencies. Also, analyses of the SKATE Scale revealed that the figure skaters perceived themselves and their coach as the most significant sources of weight loss pressures, and that this pressure was mainly for performance benefits. Correlational analyses of the three most commonly used subscales of the EDI with the five pressure sources of the SKATE Scale revealed a strong positive relationship between these two. These results are discussed in terms of the possible relationship between disordered eating tendencies and weight loss pressures, as well as practical implications and future research.
Keywords: Psychology, Social.